2014
DOI: 10.1111/joic.12128
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Vascular Responses to Resolute® and Xience V® Polymer‐Based Drug‐Eluting Stents in a Rabbit Model of Atherosclerosis

Abstract: At 3-month follow-up, nearly complete re-endothelialization was achieved for all stent groups. Xience V EES induced greater suppression of neointimal growth and peri-strut inflammation, higher vasorelaxation to acetylcholine, and expression of thrombomodulin at the level of unstented controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It was also recently reported by Holdaas and colleagues [44] that coronary artery intimal thickening and the incidence of cardiac allograft vasculopathy were significantly reduced by everolimus therapy. In combination with other clinical studies [45][46][47] , it has been shown that everolimus-eluting stents are the optimal choice for preventing vascular restenosis and the occurrence of cardiac allograft vasculopathy (CAV) after heart transplant or other cardiac surgeries.…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…It was also recently reported by Holdaas and colleagues [44] that coronary artery intimal thickening and the incidence of cardiac allograft vasculopathy were significantly reduced by everolimus therapy. In combination with other clinical studies [45][46][47] , it has been shown that everolimus-eluting stents are the optimal choice for preventing vascular restenosis and the occurrence of cardiac allograft vasculopathy (CAV) after heart transplant or other cardiac surgeries.…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…Nonetheless, a number of studies have assessed DES efficacy in this model and have shown important similarities to many aspects of the human response to stenting. 21 , 74…”
Section: Modelling Impact Of Atherosclerosis On Drug Release and Distmentioning
confidence: 99%
“…Polymer‐related causes were ascribed to release of polymer by‐products or release of degradation products from low molecular weight degradable polymers. Preclinical studies comparing the same two commercial DES coated with two different durable polymers have shown a consistent difference in the inflammatory response to the implants . As the drugs and stent platforms used are well proven, a potential explanation lies in differences in the biocompatibility or stability of the durable coatings.…”
Section: Introductionmentioning
confidence: 99%